2005
DOI: 10.1158/1078-0432.ccr-05-0859
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Global Methylation Level, Loss of Heterozygosity, and Microsatellite Instability in Sporadic Colorectal Cancer

Abstract: Purpose: The relationship between global hypomethylation, chromosomal instability (CIN), and microsatellite instability (MSI) remains unclear in colorectal cancer. The aim of this study was to investigate the relationship between global methylation status, loss of heterozygosity (LOH), and MSI in sporadic colorectal cancer. Experimental Design: We determined global methylation levels in 80 sporadic colorectal cancers, 51adjacent normal tissues, and 20 normal tissues using the long interspersed nucleotide eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
84
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 31 publications
9
84
3
Order By: Relevance
“…High-level microsatellite-unstable tumors tend to be diploid 38 and chromosomal instability is a relatively infrequent phenomenon; LOH is observed in 16-21% of cancers with high-level microsatellite instability, compared with 56-83% of microsatellite-stable tumors. [38][39][40] Hence, it has been argued that chromosomal instability is not a major mechanism for carcinogenesis in high-level microsatellite-unstable tumors. 41 Several studies have shown that chromosomal instability is an adverse prognostic factor in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-level microsatellite-unstable tumors tend to be diploid 38 and chromosomal instability is a relatively infrequent phenomenon; LOH is observed in 16-21% of cancers with high-level microsatellite instability, compared with 56-83% of microsatellite-stable tumors. [38][39][40] Hence, it has been argued that chromosomal instability is not a major mechanism for carcinogenesis in high-level microsatellite-unstable tumors. 41 Several studies have shown that chromosomal instability is an adverse prognostic factor in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…19 Hence, the infrequent occurrence of chromosomal instability may be related to the better outcome observed in tumors with high-level microsatellite instability. However, signet ring cancers were either not included in these studies 40 or the histologic details were not provided. 39 Our study shows that chromosomal instability, as manifested by LOH at one or more of the four loci studied, is present in nearly all signet ring cell carcinomas, including those with high-level microsatellite instability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in prostatic adenocarcinomas, genome-wide DNA hypomethylation by LINE-1 was associated with alterations (either loss or gain) of chromosome 8, 33 and global hypomethylation in colorectal cancers was more common in microsatellite stable tumors than in microsatellite instability-high tumors. 34 However, at least in some tumor sites, methylation of CpG islands in the promoter regions of the genes were unassociated with global hypomethylation, including colorectal neoplasms 35 and stomach cancers. 36 We did not have any survival difference with methylation levels of LINE-1 and Alu in these indolent tumors, but in a previous study of patients with acute lymphoblastic leukemia, LINE-1 hypomethylation and methylation of multiple CpG islands were independent prognostic factors for prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Global hypomethylation plays a causal role in tumor formation by promoting chromosomal instability, activation of proto-oncogenes, and loss of heterozygosity, all of which are highly correlated with tumorigenesis. [6][7][8] Genetic and epigenetic alterations following global DNA hypomethylation in noncoding regions have been shown to play a significant role in animal models and human hepatocarcinogenesis. DNA hypomethylation is one of the key events in the initiation of the carcinogenic process in animal models.…”
Section: Introductionmentioning
confidence: 99%